Retro‐foreland Basin Development in Response to Proto‐Tethyan Ocean Closure, NE Tibet Plateau. Issue 12 (11th December 2019) - Yan, Zhen; Fu, Changlei; Aitchison, Jonathan C.; Buckman, Solomon; Niu, Manlan; Cao, Bo; Sun, Yi; Guo, Xianqing; Wang, Zongqi; Zhou, Renjie
Abstract: The compositions and ages of the sediments within retro or foreland basins that are formed and preserved adjacent to collisional orogens can reflect the nature of colliding tectonic elements. The nonmarine Yaoshuiquan and Huabaoshan formations in the South Qilian belt on the NE Tibetan Plateau deposited within a retro‐foreland basin setting during latest Ordovician to Late Silurian time in response to arc‐continent collision. Detritus derivation from a Cambro‐Ordovician arc‐ophiolite complex contains mixed 530‐480 Ma oceanic‐crust together with contributions from a 479‐450 Ma continental‐arc early in development of the basin. The Cambrian arc‐accretionary system and Central Qilian block united to form the basement of a continental arc at ~450 Ma, and both then contributed sediments to the Lianhuashan‐Huabaoshan basin. After the Hualong complex accreted to the north, a broad Andean‐type margin developed along the southern margin of the Central Qilian block from 450 to 440 Ma. These processes generated a wider basin that received detritus from both the south and the north. Consumption of the Proto‐Tethyan Ocean ended with collision between the Qaidam and Hualong blocks, which led to mass wasting of detritus from the Andean‐type igneous rocks and both blocks with the basin from 440 to 420 Ma. Key Points: The Yaoshuiquan and Huabaoshan formations of the Qilian Orogen record alluvial deposition in a retro‐foreland basin The retro‐foreland basin formed in response to collision of the Qaidam block and an Andean‐type arc between 440 and 420 Ma Voluminous detritus shed from a Cambrian‐age arc‐ophiolite complex, micro‐continental block, and Andean‐type margin